The Christopher Columbus Project: An Enterprise of Modernity (2019)
The project of discovering America by Christopher Columbus is an enterprise of Modernity, understood as the modern mentality displayed in the capitalist system. Even though Columbus lived during the Renaissance period, the mentality carried in his project is closer to some modern philosophers such as Descartes and Hobbes, who from rationality and individualism constitute a change of time. The hypothesis that Columbus is a modern person is sustained with evidence in the reasons he explained to defend his project from the Spanish court and especially the final agreement, "the capitulation", in which rationality and individualism took precedence over divine or medieval considerations. The rationalist mentality of Columbus prefigures that from modern businessman who does not stitch without thimble.